Control interno de las cuentas por cobrar en la Empresa Transporlit S.A. transportes pesados del litoral en la ciudad de Guayaquil periodo 2022. - Gaibor Cadena, Evelyn Katherine (2023)
The internal control of accounts receivable in an organization is essential to be able to carry out correct management of the management policies, both of the credit portfolio and the collection process, which depends on the priority given to each one of the credit policies that the entity has. This case study has the theme of ¨Internal control of accounts receivable of the company Transporlit S. A. Transportes Pesado del Litoral in the city of Guayaquil, for the period 2022¨ and its main objective is to examine the liquidity of the accounts receivable of the company, previously mentioned company, using information collection instruments such as the internal control questionnaire, examine the accounts receivable for the indicated period, using documentary and field research methods with a qualitative approach in order to provide the most information for support the present case study.